Therapeutic plasma exchange in the intensive care unit and with the critically ill, a focus on clinical nursing considerations. Issue 4 (6th April 2022) - Baldwin, Ian; Todd, Sarah
Abstract: Therapeutic plasma exchange (TPE) is a blood purification technique removing antibodies and plasma proteins to modulate disease and promote recovery. The procedure has different methods, using a membrane or plasma separator with many elements similar to continuous renal replacement therapy (CCRT) in the Intensive Care Unit (ICU). These nursing knowledge and skill sets apply where ICU nurses are providing TPE with increasing need. However, different care models are also in place where TPE is the responsibility of apheresis and nephrology teams visiting the ICU. The plasma replacement volume and prescribing is aligned with published guidelines but is variable when critical illness overlays the primary indication for TPE. There are some important considerations for TPE with respect to anticoagulation, machine settings, prescribing, and associated nursing management. TPE can be performed concurrent with CRRT in acute situations using Y‐piece and valve connectors and is a new and recent advanced blood purification for the ICU.